POLITENESS STRATEGY USED IN REPUBLICAN DEBATE BY DONALD TRUMP - Jhon Ginever Sibarani; Leni Marlina (English Language and Literature, 2018)
Politeness strategy is a way that is done by someone to say his speech more politely. The politeness strategy can be found in daily conversations and in debating events. One of the debates of concern for this study is the debate of candidates in the Republican Party. The purpose of this paper is to describe the politeness strategies used in the Republican debate by Donald Trump. This research used the theory of politeness strategy proposed by theory is Brown and Levinson (1987) who classify politeness strategies into four types: Bald on Record, Positive Politeness, Negative Politeness, and Off Record. The finding of this study indicates that Donald Trump uses only three types of politeness strategies in Republican debate. The most prominent politeness strategy is Positive politeness (55.27%). Other politeness strategies are Negative politeness (22.98%), and Bald on Record (21.73%). It can be concluded that Donald Trump mostly uses Positive politeness strategy in delivering his speech for Republican Party debate.